Residential Schools: Creating and Continuing Institutionalization among Aboriginal Peoples in Canada - Rand, Julia (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2011)
Many Aboriginal peoples in Canada have experienced, directly or indirectly, the effects of residential schools. Some Aboriginal people have also experienced the phenomenon known as institutionalization, as a result of residential school experiences, experiences over which they had no control and that were demanded by law. Some Aboriginal people in Canada have moved from the residential school institutions to similar newly developed institutions such as shelters and to established institutions such as the correctional system, or both. Indeed, Aboriginal peoples are overrepresented in all such institutions. In this paper, I seek to demonstrate the association between Aboriginal peoples’ experiences in and of residential schools and subsequent adult institutionalization. Attempts to ‘civilize’ Aboriginal peoples through cultural assimilation may have instead resulted in intergenerational institutionalization among many Aboriginal peoples in Canada.